JULIA AND MANDELBROT SETS FOR SOME TWO-DIMENSIONAL QUADRATIC REFLECTIONS - Kutlimuratov Ravshanbek Rozboeich (Journal of Higher Education and Academic Advancement, 2024)
In this article, in the study of two-dimensional quadratic reflection, graphic analysis and phase portrait are important tools for the study of dynamic systems, and the role of this method is discussed. Also, in order to contribute to the development of the industry, various comments and suggestions were presented in the article